(untitled) (Training and Practice : Journal of Educational Sciences, 2019)
In our rapidly changing world the usage of foreign languages is getting more and more indispensable. During the application to higher education institutions the language exam certificate is rewarded by extra points, and it will be compulsory for higher education application in the near future. The coursebook market offers a wide choice of language books for schools. But the course book list issued centrally defines it for the educational institutions what kind of books their teachers can teach from. This list contains several publishers and titles, from which the schools (and teachers) have to find the most suitable one(s) (as long as they choose the option of using a coursebook at all). But how? We would have liked to examine this question in deatils through the analysis of coursebooks entitled Playway to Engish, during which – besides the analysis of the books – we have compared their content to the local curriculum of a school and asked the colleagues’ opinions about their usage in everyday life as well.